Diseminasi Penggunaan Sosial Media dalam Perluasan Sebaran Pemasaran pada Produk UMKM - Widia, Elsa (LPPPM STAI Darul Hikmah Bangkalan, 2021)
The impact of the COVID-19 pandemic on MSMEs is believed to be greater due to the high level of vulnerability due to changes in people's lifestyles. Several policies carried out by the government, such as large-scale social restrictions (PSBB), a ban on going home and the recommendation to